Ischemic optic neuropathies - Hayreh, Sohan Singh; SpringerLink (Online service). (Berlin New York Springer, 2011)
Ischemic optic neuropathy, often referred to as a stroke of the optic nerve, is one of the major causes of visual impairment or loss of vision. Yet it is a highly controversial and confusing subject because of the general lack of in-depth scientific understanding of the subject. In this book the leading authority in the field describes in detail the current knowledge about the different forms of the often devastating disease. Insights into the underlying pathogenesis and peculiar clinical features are given, leading the reader to the most appropriate way of management. This information will help any physician dealing with patients who suffer from sudden loss of vision.
Structure of the Optic Nerve -- Blood Supply of the Optic Nerve -- Blood-Optic Nerve Barrier -- Factors Influencing the Optic Nerve Head Blood Flow -- Measurement of the Optic Nerve Head Blood Flow -- Terminology and Types of Ischemic Optic Neuropathy -- Optic Disc -- Clinical Evaluation of Patients with Ischemic Optic Neuropathies -- General Characteristics of Giant Cell Arteritis -- Clinical Features of Giant Cell Arteritis -- Diagnostic Criteria for Giant Cell Arteritis -- Ophthalmic Manifestations of Giant Cell Arteritis -- Management of Giant Cell Arteritis to Prevent Visual Loss -- Pathogenesis of Classical Non-arteritic Anterior Ischemic Optic Neuropathy -- Pathogenesis of Some Controversial Non-arteritic Anterior Ischemic Optic Neuropathy Clinical Entities -- Clinical Features of Non-arteritic Anterior Ischemic Optic Neuropathy -- Management of Non-arteritic Anterior Ischemic Optic Neuropathy -- Animal Model of Non-arteritic Anterior Ischemic Optic Neuropathy -- Classification and Incidence of Posterior Ischemic Optic Neuropathy -- Pathogenesis of Posterior Ischemic Optic Neuropathy -- Clinical Features of Posterior Ischemic Optic Neuropathy -- Management of Posterior Ischemic Optic Neuropathy.
Electronic reproduction.
Keywords: Optic nerve -- Diseases; Electronic books